The Chairman's Summing Up : The IMF and the Crises in Greece, Ireland, and Portugal. (Policy Papers; Policy Paper ;, 2016)
Executive Directors welcomed the report by the Independent Evaluation Office (IEO) on the IMF and the Crises in Greece, Ireland, and Portugal, and appreciated the accompanying statement by the Managing Director. They agreed that the report's findings provide valuable insights and lessons for handling crises in members of currency unions. Directors underscored that the work of the IEO continues to play a vital role in enhancing the learning culture within the Fund, strengthening the Fund's external credibility, and supporting the Executive Board's oversight responsibilities. Directors broadly shared the general thrust of the IEO's main findings and broadly endorsed its recommendations, with some caveats.